Environmental litigation in China a study in political ambivalence - Stern, Rachel E. (Cambridge University Press, 2013)
This is a book about the improbable: seeking legal relief for pollution in contemporary China. In a country known for tight political control and ineffectual courts, Environmental Litigation in China unravels how everyday justice works: how judges make decisions, why lawyers take cases, and how international influence matters. It is a readable account of how the leadership's mixed signals and political ambivalence play out on the ground - propelling some, such as the village doctor who fought a chemical plant for more than a decade, even as others back away from risk. Yet this remarkable book shows that even in a country where expectations would be that law wouldn't much matter, environmental litigation provides a sliver of space for legal professionals to explore new roles and, in so doing, probe the boundary of what is politically possible
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Environmental law / China; Environmental law / Political aspects / China; Pollution / Law and legislation / China; Liability for environmental damages / China; Verfahren; Umweltrecht; China